Impact of Motivation and Job Satisfaction on Employees’ Performance at Central Bank of Nigeria, Awka Branch - Ohanyere, Chinelo Patience; Eboh, Obinna Solomon; Theresa, Ezeanolue Ekwutosi (Ecobankers : Journal of Economy and Banking, 2025)
The study is to understand the impact of motivation and job satisfaction on employee performance of Central Bank of Nigeria. To achieve the objectives set, primary and secondary sources data were used. Primary data was collected both from managerial and non-managerial employees of the Bank. The total population of the Bank branch is 200 from which 120 samples was taken using Convenience sampling technique. Much of the data was collected from the managerial category since this category performs the core jobs of the Bank which is to conduct monetary policy by managing the money supply, setting interest rates, and overseeing the banking system to maintain financial stability within a country. Correlation technique was employed to find out the relationship between two variables. Regression technique also was used to find out to which extent one variable affect the other using coefficient results. Correlation results for salary is 0.589, Transport benefits 0.421, medical benefits 0.395, extra duty allowance 0.421, carrier achievement 0.562, promotion benefits 0.672 and correlation for recognition is 0.407 which reveal existence of positive relationship between motivation and employees’ performance and therefore implying that the increase in motivation will lead to increase in employees’ performance. This situation insists on increasing attention to employee motivation practice in order to improve employee performance. The findings suggest enhancement of current motivation package by incorporating both intrinsic such as promotion, recognition, support for carrier achievement and extrinsic motivation factors such as salary, extra duty allowance, transport allowance, medical benefits will help optimum utilization of human resources as well as increasing employees’ performance. Furthermore there is pressing need to develop organisation motivation policy that will help the Central Bank Of Nigeria, Awka Branch management properly in handling motivation function.